Single-cell transcriptomics of human gut T cells identifies cytotoxic CD4+CD8A+ T cells related to mouse CD4 cytotoxic T cells - Tanemoto, Shun; Sujino, Tomohisa; Miyamoto, Kentaro; Moody, Jonathan; Yoshimatsu, Yusuke; Ando, Yoshinari; Koya, Ikuko; Harada, Yosuke; Tojo, Anna Okuzawa; Ono, Keiko; Hayashi, Yukie; Takabayashi, Kaoru; et al. (Frontiers in Immunology, 2022)
Cytotoxic CD4+ T cells (CD4-CTLs) show the presence of cytolytic granules, which include the enzymes granzyme and perforin. The cells have a pathogenic and protective role in various diseases, including cancer, viral infection, and autoimmune disease. In mice, cytotoxic CD4+ T cells express CD8αα+ and reside in the intestine (mouse CD4+CTLs; mCD4-CTLs). The population of cytotoxic CD4+ T cells in the human intestine is currently unknown. Moreover, it is unclear how cytotoxic CD4 T cells change in patients with inflammatory bowel disease (IBD). Here, we aimed to identify cytotoxic CD4+ T cells in the human intestine and analyze the characteristics of the population in patients with IBD using single-cell RNA-seq (scRNA-seq). In CD4+ T cells, granzyme and perforin expression was high in humanMAIT (hMAIT) cells and hCD4+CD8A+ T cell cluster. Both CD4 and CD8A were expressed in hTreg, hMAIT, and hCD4+CD8A+ T cell clusters. Next we performed fast gene set enrichment analysis to identify cell populations that showed homology to mCD4CTLs. The analysis identified the hCD4+CD8A+ T cell cluster (hCTL-like population; hCD4-CTL) similar to mouse CTLs. The percentage of CD4+CD8A+ T cells among the total CD4+ T cells in the inflamed intestine of the patients with Crohn’s disease was significantly reduced compared with that in the noninflamed intestine of the patients. In summary, we identified cytotoxic CD4+CD8+ T cells in the small intestine of humans. The integration of the mouse and human sc-RNA-seq data analysis highlight an approach to identify human cell populations related to mouse cell populations, which may help determine the functional properties of several human cell populations in mice.